A new microtubule-targeting compound PBOX-15 inhibits T-cell migration via post-translational modifications of tubulin. - Mc Elligott, Tony (My University, 2008)
The ordered, directional migration of T-lymphocytes is a key process during immune surveillance, immune response, and development. A novel series of pyrrolo-1,5-benzoxazepines have been shown to potently induce apoptosis in variety of human chemotherapy resistant cancer cell lines, indicating their potential in the treatment of both solid tumors and tumors derived from the hemopoietic system. Pyrrolobenzoxazepine 4-acetoxy-5-(1-naphtyl)naphtho[2,3-b]pyrrolo[1,2-d][1,4]-oxazepine (PBOX-15) has been shown to depolymerize tubulin in vitro and in the MCF7 breast cancer cell line. We hypothesized that this may suggest a role for this compound in modulating integrin-induced T-cell migration, which is largely dependent on the microtubule dynamics. Experiments were performed using human T lymphoma cell line Hut78 and peripheral blood T-lymphocytes isolated from healthy donors. We observed that human T-lymphocytes exposed to PBOX-15 have severely impaired ability to polarize and migrate in response to the triggering stimulus generated via cross-linking of integrin lymphocyte function associated antigen-1 receptor. Here, we show that PBOX-15 can dramatically impair microtubule network via destabilization of tubulin resulting in complete loss of the motile phenotype of T-cells. We demonstrate that PBOX-15 inhibitory mechanisms involve decreased tubulin polymerization and its post-translational modifications. Novel microtubule-targeting effects of PBOX-15 can possibly open new horizons in the treatment of overactive inflammatory conditions as well as cancer and cancer metastatic spreading.
PUBLISHED
Keywords: T-cell migration - PBOX - Tubulin